Leading Through Bias 5 Essential Skills to Block Bias and Improve Inclusion at Work - Luthra, Poornima; Muhr, Sara Louise (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2023)
"Leading through bias is paramount. Through this book, you will learn that it requires you to lead with conviction, clarity, accountability, allyship and strength. It is not an easy ride. You will need to step up and even more leadership will be required of you when everybody comes with a different view. But what you stand to gain - the value you can create both in your people and in your business - is immense. This is important." Foreword by Mette Louise Kaagaard, CEO of Microsoft Denmark & Iceland Bias is everywhere. While we cannot completely eliminate it, we can make efforts to become more aware of them, to work hard to block them, and to minimise the impact they have on our organisations and the people who work within them. By identifying 5 essential skills - conviction, clarity, accountability, allyship and strength - this book offers an all-in-one resource to help you explore the topics of inclusive leadership and the role of leaders in addressing bias within a global context. Chapters are grounded in theoretical frameworks while mini-experiences and self-reflection exercises are presented throughout, making this ideal reading for leaders. Likewise, this is a comprehensive resource for executive students, particularly as it enables students to reflect on their individual and organisational journeys towards inclusion along with key features such as additional reading and practical take-aways. Poornima Luthra, PhD (she/her) is Associate Professor at the Copenhagen Business School. An established author, Poornima has been recognised as one of the world's 30 up-and-coming thinkers whose ideas will make an important impact on management thinking in the future by the prestigious Thinkers50. Sara Louise Muhr, PhD (she/her) is Professor of Diversity and Leadership at Copenhagen Business School. She is also Academic Director of the CBS Leadership Centre and serves on the board of directors of Copenhagen Business School. Sara is the author of more than 80 journal articles and book chapters, as well as 10 published books, including Diversity and Identity in the Workplace: Connections and Perspectives published in 2018 by Palgrave.
Chapter 1: Introduction -- Chapter 2: Leading with Conviction - Believing in the Value of DEI -- Chapter 3: Leading with Clarity (Part I - Understanding the Basics of Bias and Identity Bias) -- Chapter 4: Leading with Clarity (Part II - Situation-related Cognitive Bias and the Impact of Bias) -- Chapter 5: Leading with Accountability - Addressing Systemic Bias -- Chapter 6: Leading with Allyship - Moving Beyond Tolerance and Obligation -- Chapter 7: Leading with Strength - Showing Vulnerability -- Final Thoughts -- Recommended Resources -- References.
Keywords: Diversity in the workplace; Management; Strategic planning; Leadership; Diversity Management and Women in Business; Management; Business Strategy and Leadership